An Analysis of Factors Contributing to Students’ Challenges in Learning English - Sine, Jec Krist; Hambandima, Erny Selfina Nggala; Snae, Alfred (English Education Study Program - Artha Wacana Christian University, 2025)
This study seeks to examine the factors contributing to students' challenges in learning English at SMA Negeri 4 Kupang. The central research question is: What causes students’ challenges in learning English at SMA N 4 Kupang? Employing a descriptive qualitative approach, the research focuses on understanding these challenges through the experiences of 11th-grade students during the 2024/2025 academic year. Data were gathered through interviews with 15 students who reported experiencing difficulties in learning English. The findings reveal three primary factors behind these difficulties: 1) Translation challenges, largely due to a limited vocabulary and a weak grasp of grammar. 2.) Vocabulary limitations negatively affect students' ability to communicate effectively in both spoken and written English. 3.) Low motivation, influenced by repetitive teaching methods, fear of making mistakes, and less-than-ideal class timing. In light of these findings, it is suggested that teachers implement more dynamic and interactive teaching strategies and offer greater support to boost students’ confidence. Addressing these issues could lead to more effective improvements in students’ English language proficiency.